Method for producing hydrogen and co-producing alpha-semi-hydrated gypsum by using waste gypsum

Through electrochemical hydrogen production and subsequent processes, waste gypsum is converted into high value-added α-semi-water gypsum and hydrogen, which solves the problems of high cost of waste gypsum treatment and low value-added value, and realizes efficient utilization of resources and environmentally friendly production process.

CN119640275APending Publication Date: 2025-03-18PANZHIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411807122.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing treatment technology of waste gypsum is difficult, high cost and low added value, and it has failed to effectively utilize the resource potential of waste gypsum.

Method used

Waste gypsum is stirred and beaten with water, and hydrogen is generated through electrochemical hydrogen production process. Then, α-hemihydrate gypsum is prepared through solid-liquid separation, directed transformation regulation and high-temperature drying. The entire process is powered by solar energy to reduce energy consumption.

Benefits of technology

The high-value-added resource utilization of waste gypsum is realized, and two high-value-added products, hydrogen and α-semi-water gypsum are produced, which improves the utilization efficiency of waste gypsum, reduces the treatment cost, and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640275A_ABST
    Figure CN119640275A_ABST
Patent Text Reader

Abstract

The invention discloses a method for producing hydrogen and co-producing alpha-semi-hydrated gypsum from waste gypsum, and belongs to the field of high value-added resource utilization of typical bulk solid waste. The method comprises the following steps: 1) adding water into waste gypsum, stirring and pulping to obtain slurry; 2) continuously producing hydrogen from the slurry through an electrochemical hydrogen production process to obtain hydrogen, and collecting the slurry after hydrogen production is finished; 3) removing impurities from the slurry through a solid-liquid separation process to obtain liquid; and 4) crystallizing the liquid in a crystal transformation directional regulation process, and drying at high temperature after crystallization to obtain the alpha-semi-hydrated gypsum. The method for producing hydrogen and co-producing alpha-semi-hydrated gypsum from waste gypsum is simple in process and low in raw material cost, high-added-value resource utilization of waste gypsum can be achieved, the purity of produced hydrogen is larger than 60%, the purity of co-produced alpha-semi-hydrated gypsum is larger than 98%, the whiteness is larger than 95, and the utilization efficiency of waste gypsum is larger than 80%; the method can effectively solve the problems of high difficulty, high cost, low added value and the like of the existing waste gypsum treatment technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of high value-added resource utilization of typical bulk solid waste, and specifically relates to a method for producing hydrogen from waste gypsum and co-producing alpha-hemihydrate gypsum. Background Art

[0002] At present, the output of waste gypsum continues to be at a high level. With the rapid development of industry, many industrial production processes continue to produce a large amount of waste gypsum, such as phosphogypsum produced by the production of phosphoric acid in the chemical industry and desulfurization gypsum produced by desulfurization in power plants. Taking my country as an example, the annual production of desulfurization gypsum reaches tens of millions of tons, and the emission of phosphogypsum is also extremely large. The generation of these waste gypsums is, on the one hand, an inevitable product of industrial development, and on the other hand, it also brings great pressure to the environment. The accumulation of a large amount of waste gypsum not only occupies a large amount of land resources, but also may cause environmental pollution due to factors such as wind and rain, such as soil and water pollution, and may even cause some potential risks such as geological disasters. However, with the continuous improvement of environmental awareness and the gradual improvement of relevant policies, the treatment and utilization of waste gypsum have begun to receive more and more attention.

[0003] At present, the comprehensive utilization of waste gypsum has made certain progress. Many enterprises and scientific research institutions are actively exploring ways to utilize waste gypsum and transform it into valuable products. In the field of building materials, waste gypsum can be used to produce building materials such as gypsum boards and gypsum blocks, which not only realizes the recycling of resources, but also reduces the construction industry's dependence on natural gypsum. At the same time, in cement production, waste gypsum can be used as a retarder to improve the performance of cement. In addition, waste gypsum also has certain applications in the fields of soil improvement and environmentally friendly materials. But overall, the comprehensive utilization of waste gypsum still faces some challenges, such as the need to improve technical level, low market recognition, and high transportation costs. It is necessary to further strengthen technical research and development to improve the comprehensive utilization rate of waste gypsum.

[0004] With the increasing awareness of environmental protection and the continuous increase in energy demand, hydrogen energy, as a clean, efficient and renewable energy source, has received more and more attention. Hydrogen can be used as a fuel, energy storage medium and chemical raw material for many purposes, and is widely used in industry, transportation, household and other fields. However, the traditional hydrogen preparation method has problems such as high energy consumption, high cost and pollutant emissions, which restricts the development of hydrogen energy. Therefore, developing a low-cost and high-efficiency hydrogen preparation technology is one of the current research hotspots. With the upgrading of energy security and industrial transformation, the status of the hydrogen energy industry is becoming increasingly apparent. As the most ideal form of hydrogen energy utilization, green hydrogen is the main direction of future hydrogen energy development. Green hydrogen refers to the production of hydrogen by electrolysis of water through renewable energy such as photovoltaic and wind power. The hydrogen production process does not produce greenhouse gases and is also called "zero-carbon gas". There are many technical green lines for the preparation of green hydrogen, including alkaline water electrolysis technology (ALK), cation exchange membrane water electrolysis technology (PEM), solid oxide water electrolysis technology (SOEC), anion exchange membrane water electrolysis technology (AEM), as well as a series of hydrogen production technologies including photochemical hydrolysis, thermochemical hydrolysis, biomass reforming, and microbial electrolyzers. However, the existing hydrogen production technology has the problems of complex equipment, high cost, complex raw material pretreatment process and complex hydrogen production reagents, and high cost. Therefore, it is necessary to develop a hydrogen production method with low equipment investment cost and simple reagents.

[0005] Faced with the global resource and energy crisis, how to turn solid waste into resources and energy has become one of the main research tasks in contemporary times. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the existing treatment technology for waste gypsum is difficult, costly, and has low added value, and a new approach to the resource utilization of waste gypsum is not provided.

[0007] The technical solution adopted by the present invention to solve the technical problem is:

[0008] In order to realize the dual recovery of energy and resources, the present invention provides a method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum, comprising the following steps:

[0009] (1) adding water to waste gypsum, stirring and slurrying to obtain waste gypsum slurry;

[0010] (2) The waste gypsum slurry is subjected to an electrochemical hydrogen production process to continuously produce hydrogen to obtain hydrogen gas, and the slurry after hydrogen production is completed is collected;

[0011] (3) removing impurities from the slurry after hydrogen production through a solid-liquid separation process to obtain a liquid after impurities removal;

[0012] (4) After impurities are removed, the liquid enters the crystal transformation and directional control process for crystallization, and after crystallization, it is dried at high temperature to obtain α-hemihydrate gypsum.

[0013] Wherein, in step (1) of the above method, the waste gypsum includes one or more of phosphogypsum, flue gas desulfurization gypsum, titanium gypsum, fluorite, natural gypsum, red gypsum and sulfur gypsum.

[0014] Wherein, in step (1) of the above method, the mass ratio of waste gypsum to water is 1:10-50, and the mixture is stirred at a speed of 150-600 rpm for 15-30 min.

[0015] Among them, in step (2) of the above method, the electrochemical hydrogen production process adopts a double-walled electrolyzer, the hydrogen production voltage is 5 to 72V, and the continuous hydrogen production time is 3 to 6 hours.

[0016] Furthermore, the anode electrode of the double-walled electrolytic cell is the inner wall of the electrolytic cell, the distance between the walls is 3 to 20 cm, the interlayer of the double-walled electrolytic cell contains pure water, a plurality of cathode electrodes are evenly distributed in the inner tank of the electrolytic cell, and the inner tank of the electrolytic cell contains waste gypsum slurry;

[0017] The anode electrode is an alloy, ruthenium-iridium-titanium or titanium electrode;

[0018] The cathode electrode is a graphite, alloy, ruthenium-iridium-titanium, iron, platinum, nickel or titanium electrode, and is in the shape of a thorn, needle, layer or spiral.

[0019] Wherein, in step (2) of the above method, the purity of the obtained hydrogen is greater than 60%.

[0020] Among them, in step (3) of the above method, the solid-liquid separation process adopts a membrane separation rotating barrel, the rotation speed of the inner barrel is 15 to 60 rpm, and the air pressure of the outer barrel is -0.1 to -1.5 MPa.

[0021] Furthermore, the inner barrel of the above-mentioned membrane separation rotating barrel is formed by multiple layers of nested membrane materials, and the membrane materials include ceramic materials, fiber membrane materials, polytetrafluoroethylene membranes, nylon membranes or polyethersulfone membranes.

[0022] Among them, in step (4) of the above method, the pressure of the crystallization directional control process is 0.1-2.5MPa, the temperature is 90-150°C, and the time is 15-60min; after the crystallization, the liquid is kept warm and enters high-temperature drying, and the drying temperature is 60-100°C.

[0023] Wherein, in step (4) of the above method, the purity of the obtained α-hemihydrate gypsum is greater than 98% and the whiteness is greater than 95.

[0024] Among them, in the above-mentioned method of producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum, the entire process is powered by solar energy.

[0025] The beneficial effects of the present invention are as follows: the present invention uses industrial waste gypsum as the main raw material, and the waste gypsum has a slightly soluble property. Under electrochemical conditions, the activity of the aqueous solution can be increased, and the solubility of the waste gypsum can be increased. The dissolved waste gypsum is dissociated into Ca 2+ and SO4 2- , SO4 2- will move toward the anode, Ca 2+ Moving toward the cathode, Ca 2+ and SO4 2- It acts as a strong electrolyte. In addition, it will strengthen water dissociation under electrochemical conditions and produce H2 in the cathode area. The present invention evenly arranges multiple cathode electrodes in the core of the electrolytic cell, and the anode electrode is the inner wall of the electrolytic cell. Pure water is placed in the interlayer of the double-walled electrolytic cell, which strengthens the production of H2; after strengthening the dissolution of Ca 2+ and SO4 2- Under the action of the electric field force, the lattice elements will be evenly distributed. After the insoluble impurities are removed, they enter the crystal transformation and directional control process for crystallization, and then are prepared into α-hemihydrate gypsum through high-temperature drying. The energy source of the entire process is solar energy, which greatly reduces energy consumption and realizes the independent closed-loop high-value-added resource utilization of waste gypsum, while producing two high-value-added products, H2 and α-hemihydrate gypsum.

[0026] From an environmental protection perspective, this method uses waste gypsum as the only raw material and is an in-situ treatment, which realizes large-scale high-value-added resource processing of waste gypsum, reduces the pollution risk of waste gypsum to the ecological environment, and produces two high-value-added products, H2 and α-hemihydrate gypsum, which greatly improves the high-value-added resource utilization rate of waste gypsum; the impurities generated in the impurity removal process are mainly SiO2 components, which can be used as raw materials for the production of microcrystalline glass, and the liquid phase can be recycled, and the entire process achieves clean production.

[0027] This method can provide a feasible path for the high-value-added resource processing of waste gypsum, reduce processing costs, and promote the sustainable development of industry. In addition, this method can also drive the development of related industries, such as the solid waste treatment industry and the materials industry, and create more employment opportunities and economic benefits.

[0028] The method of producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum of the present invention has a simple process and low raw material cost, and can realize high value-added resource utilization of waste gypsum. The purity of the generated hydrogen is greater than 60%, the purity of the co-produced α-hemihydrate gypsum is greater than 98%, the whiteness is greater than 95, and the utilization efficiency of the waste gypsum is greater than 80%. The present invention can not only solve the problem of waste gypsum treatment, but also provide a feasible and low-cost application path for resource and energy recovery, realize the recycling of resources, and has broad development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the process of the present invention;

[0030] Figure 2 Product testing for the co-production of α-hemihydrate gypsum from hydrogen production from phosphogypsum;

[0031] Figure 3 Product testing for flue gas desulfurization gypsum hydrogen production and co-production of α-hemihydrate gypsum;

[0032] Figure 4 Product testing for hydrogen production from titanium gypsum and co-production of α-hemihydrate gypsum. DETAILED DESCRIPTION

[0033] The technical solution of the present invention can be specifically implemented in the following manner.

[0034] The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum of the present invention has a process flow diagram as shown in FIG. Figure 1 As shown. The process method mainly includes five stages: transportation and re-slurry of waste gypsum, multi-cathode electrochemical hydrogen production, removal of insoluble impurities, crystallization directional control and high-temperature drying. The transportation and re-slurry are mainly transported to the agitator by crawler belts, and a certain amount of water is added to form waste gypsum slurry; the waste gypsum slurry enters the multi-cathode electrochemical hydrogen production stage, which is mainly a double-walled electrolytic cell, the inner tank is an anode electrode, the wall is mainly pure water, and the inner tank is evenly distributed with multiple cathode electrodes, which mainly holds the waste gypsum slurry and strengthens hydrogen production through multiple cathodes; the waste gypsum slurry after electrochemical hydrogen production treatment enters solid-liquid separation, in which a membrane separation rotary barrel is used to remove insoluble impurities, and the outer periphery of the drum is in a negative pressure state, which is convenient for solid-liquid separation, and the drum material is mainly high-strength membrane material; the separated solids are mainly impurities such as silicon dioxide and heavy metals, which can be used to prepare microcrystalline glass; the separated liquid part contains a large amount of calcium ions and sulfate ions and enters the crystallization directional control process, and crystallizes under high temperature and high pressure. After the crystallization, it enters the high-temperature drying stage to obtain α-hemihydrate gypsum.

[0035] Preferably, in the above method, the waste gypsum mainly includes one or more of phosphogypsum, flue gas desulfurization gypsum, titanium gypsum, fluorite, natural gypsum, red gypsum and sulfur gypsum.

[0036] Preferably, the waste gypsum re-slurry solid-liquid ratio (mass ratio) in the above method is 1:10-50, and is stirred in a stirrer at a speed of 150-600 rpm for 15-30 minutes.

[0037] Preferably, the anode electrode material in the above method is an alloy, ruthenium-iridium-titanium, or titanium electrode.

[0038] Preferably, the cathode electrode in the above method is a graphite, alloy, ruthenium iridium titanium, iron, platinum, nickel, or titanium electrode, which is mainly in the shape of thorns, needles, layers, or spirals and is evenly distributed in the inner electrolytic cell.

[0039] Preferably, the voltage of the electrochemical hydrogen production in the above method is 5 to 72V.

[0040] Preferably, the distance between the walls of the double-walled electrolytic cell in the above method is 3 to 20 cm, and the inner wall is the electrolytic anode.

[0041] Preferably, the insoluble impurities in the above method are removed by using a membrane separation rotating barrel, the inner barrel rotates at a speed of 15 to 60 rpm, the inner barrel material is mainly membrane material, including one of ceramic material, fiber membrane material, polytetrafluoroethylene membrane, nylon membrane, and polyethersulfone membrane, which are nested in multiple layers; the outer barrel is fixed, and negative pressure is applied to the outer barrel to enhance solid-liquid separation.

[0042] Preferably, the crystal orientation control pressure in the above method is 0.1-2.5 MPa, the temperature is 90-150° C., and the time is 15-60 min.

[0043] Preferably, the drying temperature in the above method is mainly generated by electromagnetic heating, and the temperature is 60-100° C. After the slurry comes out of the crystallization stage, it is kept warm and enters the drying stage to prevent secondary hydration reaction.

[0044] Preferably, the electricity source for the entire technical process described in the above method all comes from solar power generation.

[0045] Preferably, the multi-cathode electrochemical hydrogen production described in the above method continuously produces hydrogen for 3 to 6 hours, and the purity of the generated hydrogen is greater than 60%.

[0046] Preferably, the co-produced α-hemihydrate gypsum in the above method has a purity greater than 98%, a whiteness greater than 95, and a utilization efficiency of waste gypsum greater than 80%.

[0047] The technical solution and effects of the present invention are further illustrated below through practical examples.

[0048] Example

[0049] A method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum, according to Figure 1 The equipment is constructed. The process of Examples 1 to 3 specifically includes the following steps:

[0050] 1. Transportation and re-slurry of waste gypsum: The waste gypsum is transported to the mixer by a crawler, water is added at a solid-liquid ratio (mass ratio) of 1:10 to 50, and the mixture is stirred at a speed of 150 to 600 rpm for 15 to 30 minutes in the mixer to prepare a waste gypsum slurry; the specific process parameters of Examples 1 to 3 are shown in Table 1.

[0051] Table 1 Repulping process parameters

[0052] Example 1 Example 2 Example 3 Types of waste gypsum Phosphogypsum Flue gas desulfurization gypsum Titanium plaster Solid-liquid ratio 1:10 1:30 1:50 Stirring speed 150rpm 300rpm 600rpm Mixing time 15min 30min 20min

[0053] 2. Electrochemical hydrogen production: The slurry in the agitator flows into the inner tank (anode electrode) of the double-layer electrolyzer along the pipeline, water is added to the electrolytic layer wall, and after the multiple cathode electrodes are evenly distributed, the anode electrode is connected to the positive electrode of the DC power supply, the cathode electrode is connected to the negative electrode of the DC power supply, and the entire electrolyzer is sealed after connecting to the hydrogen collection pipe; a voltage of 5 to 72 V is applied to produce hydrogen; the specific process parameters of Examples 1 to 3 are shown in Table 2.

[0054] Table 2 Electrochemical hydrogen production process parameters

[0055] Example 1 Example 2 Example 3 Anode electrode alloy Ruthenium Iridium Titanium titanium Cathode electrode graphite alloy Ruthenium Iridium Titanium Cathode electrode shape Thorn-shaped Layered Spiral Electrolytic cell wall spacing 3cm 20cm 10cm Voltage 5V 36V 72V

[0056] 3. Removal of insoluble impurities: The slurry after hydrogen production flows into the impurity membrane separation rotating barrel, and the outer cylinder is subjected to negative pressure of -0.1 to -1.5 MPa to enhance solid-liquid separation. The solid part is mainly impurities such as SiO2, and microcrystalline glass can be prepared. The specific process parameters of Examples 1 to 3 are shown in Table 3.

[0057] Table 3 Process parameters for removal of sparingly soluble impurities

[0058] Example 1 Example 2 Example 3 Membrane material Ceramic Materials Fiber membrane material Polyethersulfone membrane Negative pressure -0.1MPa -1.5MPa -1MPa Drum rotation speed 15rpm 60rpm 30rpm

[0059] 4. Crystallization directional control: The liquid part after solid-liquid separation enters the crystallization autoclave with a pressure of 0.1-2.5 MPa, a temperature of 90-150° C., and a time of 15-60 min. The specific process parameters of Examples 1-3 are shown in Table 4.

[0060] Table 4 Process parameters for crystal orientation control

[0061] Example 1 Example 2 Example 3 pressure 0.1MPa 2.5MPa 1MPa temperature 90℃ 150℃ 100℃ time 15min 60min 30min

[0062] 5. High temperature drying: After the crystallization is completed, the mixed liquid directly enters the high temperature drying system, which is mainly generated by electromagnetic heating at a temperature of 60 to 100°C; the dried solid is α-hemihydrate gypsum, and the water vapor is condensed and circulated to the agitator for use; the specific process parameters of Examples 1 to 3 are shown in Table 5.

[0063] Table 5 High temperature drying process parameters

[0064] Example 1 Example 2 Example 3 temperature 60℃ 100℃ 80℃

[0065] 6. Test of products obtained by the method of producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum in Examples 1 to 3, specifically as follows Figures 2 to 4 The detection results of hydrogen and α-hemihydrate gypsum obtained by co-production are shown in Table 6.

[0066] Table 6 Product test results

[0067] Example 1 Example 2 Example 3 α-hemihydrate gypsum purity 98% 99% 99% α-hemihydrate gypsum whiteness 95 98 97 Hydrogen purity 60% 75% 70% Hydrogen production time 6h 4h 3h

Claims

1. A method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum, characterized in that: The steps include: (1) adding water to waste gypsum, stirring and slurrying to obtain waste gypsum slurry; (2) The waste gypsum slurry is subjected to an electrochemical hydrogen production process to continuously produce hydrogen to obtain hydrogen gas, and the slurry after hydrogen production is completed is collected; (3) removing impurities from the slurry after hydrogen production through a solid-liquid separation process to obtain a liquid after impurities removal; (4) After impurities are removed, the liquid enters the crystal transformation and directional control process for crystallization, and after crystallization, it is dried at high temperature to obtain α-hemihydrate gypsum.

2. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 1, characterized in that: In step (1), the waste gypsum includes one or more of phosphogypsum, flue gas desulfurization gypsum, titanium gypsum, fluorite, natural gypsum, red gypsum and sulfur gypsum.

3. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 1, characterized in that: In step (1), the mass ratio of waste gypsum to water is 1:10-50, and the mixture is stirred at a speed of 150-600 rpm for 15-30 min.

4. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 1, characterized in that: In step (2), the electrochemical hydrogen production process uses a double-walled electrolyzer, the hydrogen production voltage is 5 to 72 V, and the continuous hydrogen production time is 3 to 6 hours.

5. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 4, characterized in that: The anode electrode of the double-walled electrolytic cell is the inner wall of the electrolytic cell, the distance between the walls is 3 to 20 cm, the interlayer of the double-walled electrolytic cell contains pure water, a plurality of cathode electrodes are evenly distributed in the inner tank of the electrolytic cell, and the inner tank of the electrolytic cell contains waste gypsum slurry; The anode electrode is an alloy, ruthenium-iridium-titanium or titanium electrode; The cathode electrode is a graphite, alloy, ruthenium-iridium-titanium, iron, platinum, nickel or titanium electrode, and is in the shape of a thorn, needle, layer or spiral.

6. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 1, characterized in that: In step (2), the purity of the obtained hydrogen is greater than 60%.

7. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 1, characterized in that: In step (3), the solid-liquid separation process adopts a membrane separation rotating barrel, the inner barrel rotation speed is 15 to 60 rpm, and the outer barrel air pressure is -0.1 to -1.5 MPa.

8. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 7, characterized in that: The inner barrel of the membrane separation rotating barrel is formed by nesting multiple layers of membrane materials, and the membrane materials include ceramic membrane materials, fiber membrane materials, polytetrafluoroethylene membranes, nylon membranes or polyethersulfone membranes.

9. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 1, characterized in that: In step (4), the pressure of the crystallization orientation control process is 0.1-2.5 MPa, the temperature is 90-150°C, and the time is 15-60 min; after the crystallization, the liquid is kept warm and enters high-temperature drying, and the drying temperature is 60-100°C.

10. The method for producing hydrogen from waste gypsum and co-producing α-hemihydrate gypsum according to claim 1, characterized in that: In step (4), the purity of the obtained α-hemihydrate gypsum is greater than 98% and the whiteness is greater than 95.